Respuesta :

Answer:

x = -9

y = 35/7

Step-by-step explanation:

Given equations :-

-7y - 4x = 1 ....... ( i )

7y - 2x = 53 ........ ( ii )

From ( i )

-7y = 1 + 4x

[tex]y = \frac{ - (1 + 4x)}{7} [/tex]

..........( iii )

From ( ii )

7y - 2x = 53

7y = 53 + 2x

[tex]y = \frac{53 + 2x}{7} [/tex]

.......( iv )

Equating both ( iii ) & ( iv )

y = y

[tex] \frac{ - (1 + 4x)}{7} = \frac{53 + 2x}{7} [/tex]

-(1 + 4x ) = 53 + 2x

-1 -4x = 53 + 2x

-1 - 53 = 2x + 4x

-54 = 6x

-54/6 = x

-9 = x

Also,

[tex]y = \frac{ - (1 + 4x)}{7 } \\ \\ y = - \frac{(1 + 4( - 9))}{7} [/tex]

[tex]y = - \frac{ (1 - 36)}{7} \\ \\ y = - \frac{( - 35)}{7} \\ \\ y = \frac{35}{7} [/tex]